(untitled) (El Hilo de la Fabula, 2022)
This work proposes, on the one hand, to rescue the production of Cesarina Lupati, Italian writer and journalist (1877-1957), and, on the other hand, to analyze the texts related to her trips to Argentina between 1908 and 1912, approximately, among which they mainly include Vita argentina. Argentina e Italiani al Plata osservati da una donna italiano (1910) and some scattered articles in newspapers and magazines.The objective is to recover a submerged and marginalized production in both cultural spaces, paying particular attention to its singularity and its position in regards to the Italian ‘e(im)migratory’ phenomenon in Argentina. It is hoped to reconstruct from comparative perspectives the different identity representations and ideological perspectives of this writing and, specifically, to delineate the configurations of the discursive genre related to travel and declined by the female voice.